2008
DOI: 10.1002/adsc.200700570
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Highly Enantioselective Conjugate Addition of Aldehydes to Alkylidine Malonates

Abstract: The first highly enantioselective, direct organocatalytic conjugate addition of unmodified aldehydes to alkylidinemalonates is presented. The reaction gives access to b-formyl-substituted malonates and highly functionalized lactones with up to 14:1 dr and generally 94 to > 99% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 58 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…This reaction was highly trans selective in the formation of 2-substituted cyclopentanecarbaldehydes (65), and also tolerated aryl and alkyl substituents on the enone, as well as the presence of heteroatoms (Scheme 5.34).…”
Section: Other Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction was highly trans selective in the formation of 2-substituted cyclopentanecarbaldehydes (65), and also tolerated aryl and alkyl substituents on the enone, as well as the presence of heteroatoms (Scheme 5.34).…”
Section: Other Reactionsmentioning
confidence: 99%
“…In 2008, Córdova and coworkers developed an elegant aldehyde addition to alkylidene malonates, catalyzed by the diphenylprolinol derivative XXVI [65]. The reaction furnished the corresponding 1,4 addition products in outstanding yields and enantioselectivities, and with good diastereoselectivities (Scheme 5.37).…”
Section: Other Reactionsmentioning
confidence: 99%
“…In 2001, Barbas and coworkers reported the first asymmetric conjugate additions of ketones to alkylidene malonates in moderate to good enantioselectivities using pyrrolidine‐based organocatalyst . Some groups demonstrated the asymmetric Michael addition of ketones to alkylidene malonates using pyrrolidine‐derived urea or thiourea catalyst and sulfonamide organocatalysts . On the contrary, Wang et al reported a thiourea‐sulfonamide organocatalyst that rapidly promoted the conjugate addition of 1,3‐diketones to nitroalkenes.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Some groups demonstrated the asymmetric Michael addition of ketones to alkylidene malonates using pyrrolidine-derived urea or thiourea catalyst and sulfonamide organocatalysts. [35][36][37][38][39][40] On the contrary, Wang et al 41 reported a thiourea-sulfonamide organocatalyst that rapidly promoted the conjugate addition of 1,3-diketones to nitroalkenes. Thiourea-sulfonamide organocatalysts bearing multiple hydrogen bonding donors were able to efficiently accelerate asymmetric reactions, improving yields and enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an organocatalytic4 route was developed with satisfactory results for the direct addition of ketones or aldehydes to activated olefins, especially to nitroolefins5 as well as to α,β‐unsaturated aldehydes,6 ketones,7 and sulfones8. The addition of the same donors9 to alkylidene malonates is beginning to be realized but is still underdeveloped in terms of generality, efficacy, and selectivity 10,11. Recently, a number of efforts have been made by others10 and us11 to address some of the issues with the addition of a ketone or aldehyde to alkylidene malonates with the use of organocatalysts.…”
Section: Introductionmentioning
confidence: 99%